Pengaruh Komunikasi Organisasional, Budaya Kerja, dan Kepemimpinan Partisipatif Terhadap Semangat Kerja dengan Kepuasan Kerja di Dinas Perindustrian dan Perdagangan Kabupaten Kerinci - Kurniati, Era Tri Suci; Yulasmi, Yulasmi; Lusiana, Lusiana (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the extent of the influence of organizational communication, work culture, and participative leadership on work enthusiasm with job satisfaction at the Department of Industry and Trade of Kerinci Regency. The type of research used is quantitative through a survey method. The data collection method was conducted by distributing questionnaires, with a sample of 76 respondents. The analysis method used is structural equation modeling using SmartPLS. The results showed a significant effect of organizational communication on job satisfaction. There was a significant effect of work culture on job satisfaction. There was a significant effect of participative leadership on job satisfaction. There was an insignificant effect of organizational communication on work morale. There was an insignificant effect of work culture on work morale. There was an insignificant effect of participative leadership on work morale. There was a significant effect of job satisfaction on work morale. Job satisfaction mediated the effect of organizational communication on work morale. Job satisfaction mediated the effect of work culture on work morale. Job satisfaction did not mediate the effect of participative leadership on work morale